Artificial Intelligence (AI) Utilization among Criminology Students: Its Influence on Research Productivity and Academic Performance - Madridano, Christian; Carizo, Arnel; Ayende, Larry; Clutario, Frenzy Rose; Gacusan, Iana Christine; Padua-Rentoy, Jevene; Prima, Julius; Arandia, Salvador; Bolante, Raul; Balares, Marilyn; Villar-Moralde, Mary Grace; Sambo, Rezaldy Jose; et al. (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the utilization of Artificial Intelligence (AI) among fourth-year criminology students in selected higher education institutions in the Province of Albay and its influence on research productivity and academic performance. Anchored on Connectivism, the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2), and Cognitive Load Theory, the study employed a quantitative-descriptive research design using a validated survey questionnaire. The respondents were 121 fourth-year criminology students selected from a population of 174 through stratified random sampling. Data were analyzed using frequency, percentage, weighted mean, ranking, and composite mean. Findings revealed that AI utilization in research productivity was interpreted as “Sometimes,” with grammar and plagiarism checking as the most frequently used function. ChatGPT was the most frequently used AI-based learning tool, followed by Canva, Gemini AI, QuillBot, and Cici/Dola. AI had a high influence on research productivity, particularly in improving research efficiency and research quality, while its impact on research originality was moderate. In terms of academic performance, AI had a high influence, especially on learning understanding and academic productivity, although general AI usage showed only moderate impact. The study concludes that AI serves as a useful support mechanism in criminology education, particularly for writing improvement, lesson clarification, research assistance, and academic task completion, but it does not replace critical thinking, originality, and traditional learning. The study recommends structured AI training, institutional guidelines, AI disclosure procedures, and supervised academic activities to promote responsible use. The study supports SDG 4, SDG 8, SDG 9, SDG 16, and SDG 17 by promoting quality education, AI literacy, innovation, institutional integrity, and collaborative policy development. Its sustainability impact lies in strengthening educational, technological, institutional, and governance practices for ethical and responsible AI integration in criminology education.
Keywords: Academic Performance; Artificial Intelligence; Criminology Education; Learning Understanding; Research Productivity; Responsible AI Integration; SDGs; Sustainability